Termination of the railroad: violation of good living and the Right to the City, Tierra Blanca, Veracruz, Mexico - Morales Alvarado, Ana Lourdes (2024)
For the people of Tierra Blanca, the construction of the first railway section and the subsequent creation of the railway station in the town was synonymous with progress, connection, trade and mobilization of both people and their goods. What happens in a city, when a place that was an economic bastion and at the same time a space for social interaction is terminated? The objective of this work was to scrutinize the current socio-territorial identity as a result of the transformation of its Good Living, that is, how a people reconfigures itself from a collection of historical memories and collective myths, from two dimensions: the Right to the city and Good Living. The qualitative methodology was used, with the application of narrative interviews to direct and indirect former employees of the station. As a conclusion and relevant finding, it is affirmed that the termination of Railways of Mexico effectively aggravated the way in which the inhabitants understood their Buen Vivir and the way in which they considered their right to their city. The reconfiguration of its space, in it of the defense - by its social actors - on the legitimacy of having its "lived city".